(untitled) (Defense and Security Studies, 2022)
Cybersecurity is an important topic for Industry 4.0, which will face a lot of non-traditional challenges before it can be fully implemented to help society. The objective of the study is to recognize recent cybersecurity trends, newly occurring threats and challenges as well as their potential solutions. The articles reviewed in the paper are found through science direct, Scopus, Semantic scholar and google scholar. After reviewing them, ideas from articles were grouped together to show how different articles had similar thoughts. Through the analysis of 70 articles, it was found that cybersecurity still needs a lot of improvement in order to efficiently implement Industrial Internet of Things (IIoT), especially since many articles underline the need for security-by-design approach, followed by regular updating. Key challenges are lack of awareness and security experts, increased cybercriminal and the fact that the chain is as only as strong as its weakest point. Some of the most important solutions include incorporating security into design, stronger encryption, regular updates to patch vulnerabilities and good prevention and detection mechanisms. Once cybersecurity challenges are overcome, Industry 4.0 will be able to bloom to its full extent.